4 - Science and Education in Mexico: Lessons for Africa from the Transition from National Capitalism to the Crisis of Globalisation - Aboites, Hugo (Journal of Higher Education in Africa, 2006)
Almost two decades have passed since governments in Latin American, African and Asian countries were lured by capitalism in crisis to take their populations through the new course of modernisation and globalisation. The case of Mexico represents a good example of why and how this transition took place, why it is not working and what alternative perspectives are emerging. Seen from a point of view of knowledge in society, as is the intention here, this history is even more revealing. This paper shows how science and education, including research and schools, were first called on to play an important role in the nation-building experiment of na- tional capitalism and how, when deprived of any clear social mandate, they have been left to float aimlessly in the market streams, independent social subjects that emerged from the contradictions of a globalising model of capitalist development. At the same time I argue that some recent developments, notably the Zapatista uprising in the southern state of Chiapas and the impetus this has given for the creation of new responses to globalisation and new organizations of academics, students and worker, are creating spaces of autonomy which were once inconceiv- able. I conclude that the resistance to neo-liberal policies can be decisively sup- ported by social forces arising from science and education.